Electrochemical pesticide sensor based on Langmuir-Blodgett film of cobalt phthalocyanine-anthraquinone hybrid - Ipek, Yeliz; Sener, M. Kasim; Koca, Atif (WORLD SCI PUBL CO INC, 2015)
A cathode active and selective pesticide electrochemical sensor based on Langmuir-Blodgett (LB) film of cobalt phthalocyanine-anthraquinone hybrid (CoPc-AQ) was constructed for the first time in this study. Cobalt-based, Pc ring-based, and anthraquinone-based reduction processes of CoPc-AQ indicated suitability of the complex as a possible electrochemical catalyst and sensor for detection of target species. LB film of CoPc-AQ on ITO (ITO/CoPc-AQ electrode) was titrated with eserine and carbofuran pesticides and interaction of the electrode with these pesticides was tested with square wave voltammetry (SWV), electrochemical impedance spectroscopy (EIS), and double potential step chronocoulometry (DPSCC) techniques. ITO/CoPc-AQ electrode selectively sensed carbofuran and eserine pesticides. While ITO/CoPc-AQ electrode senses carbofuran with the voltammetric responses recorded at anodic potentials (1.20 V), eserine sensing affected antraquinone based reduction peaks recorded at cathodic potentials (-0.80 V). Modification of ITO/CoPc-AQ electrode with nano-platinum and nano-gold particles (ITO/CoPc-AQ-nPt and ITO/CoPc-AQ-nAu) increased the sensitivity of the electrode. All basic sensor parameters of modified electrodes were derived with different measurement techniques and compared with each other. The lowest detection limit (2.30 x 10(-9) M) was recorded with EIS techniques on ITO/CoPc-AQ-nPt electrode for sensing of eserine.
Keywords: electrochemistry; pesticide biosensor; phthalocyanine; anthraquinone; cobalt; CARBON-PASTE ELECTRODE; ACETYLCHOLINE ESTERASE; ELECTROCATALYTIC DETERMINATION; TITANYL PHTHALOCYANINES; CARBAMATE PESTICIDES; GRAPHENE OXIDE; BIOSENSOR; COMPOSITE; CARBARYL; ORGANOPHOSPHATE; Chemistry